EFFECT of DG Optimizing on overload Transmission line Stability - Ali, A.; Abdalla, Ahmed N.; Ruhaizad, Ishak (EDP Sciences, 2018)
Typical steady state studies always treat the peak power demands as the worst case conditions. Periods of light load are also critical in the assessment of the possible state of a power system. While heavy load conditions are generally associated with overload, low voltage and generation deficiency, light load conditions may give rise to over-voltage and undesirable reactive power requirements at generation side. This paper focus on study the effect of DG Optimizing on overload Transmission line Stability. The system dispatch constraints should be taken into account to compensate or varying DG generation output and to enhance the operational performance of power systems. This dispatching operation depends on the change of DG generation and the dispatching strategy. The impact of DG generation uncertainty is limited with the generation dispatching operation and should not be neglected in system analysis.